Synergity and Community Empowerment in Organic Waste Management in Wringinanom, Gresik - Indra Pratama Putra Salmon; Abdurrahman Rahim Thaha (Ilomata International Journal of Social Science, 2023)
This research aims to examine the processing of organic waste into useful products for the community. Departing from the high volume of organic waste produced (61.97 kg per RT per day) along with bad impacts, the strategy used is the processing of waste followed by the dissemination of processing results by the composter method. This research used is descriptive analytic and participatory rural appraisal (PRA) approach which aims to encourage community participation in program implementation. This research was carried out in Pasinan Lemah Putih Village, Wringinom Subdistrict, Gresik Regency by collaborating with several stakeholders, namely the local village government, community, and implementor/expert/academic team. Data source in the form of narratives resulting from discussions and observations, secondary data, and documentation. The results show that the processing of organic waste can reducing waste volume per day and adverse effects. From an economic perspective (livelihood), processed organic waste is capable of producing 15-20 liters of liquid organic fertilizer (POC) valued at IDR 975,000 to IDR 6,000,000 in one RT per day. From a social and environmental perspective, organic waste processing, which is continued with dissemination, has provided environmental insights and new experiences for all levels of society in Pasinan Lemah Putih Village in the form of improving the quality of life of the community, the spirit of preserving environmental beauty, the spirit of preventing littering, and reducing the adverse effects of waste such as bad smell and disease.